Investment Strategies of GCC Sovereign Wealth Funds: Aligning National Development and Geopolitical Goals - Conners, Roy (AUC Knowledge Fountain, 2024)
This thesis examines how Gulf Cooperation Council (GCC) Sovereign Wealth Funds (SWFs) prioritize and implement investment strategies in the context of national development and geopolitical dynamics. Using a qualitative case study approach, it analyzes the assets, key industries, leadership, and historical evolution of major GCC SWFs (ADIA, Mubadala, ADQ, QIA, and PIF) based on publicly made available information. The findings show that GCC SWFs prioritize investments in strategic sectors, geographical destinations, and the private sector. These investments align closely with their respective national development plans, such as 'We the UAE 2031', Qatar National Vision 2030, and Saudi Arabia’s Vision 2030. Additionally, the findings reveal a linkage between GCC SWF investment strategies and their countries' respective geopolitical aspirations. In terms of implementation, the research shows that GCC countries heavily incorporate the ruling elite into positions of authority within their SWFs to integrate investment strategies with national ambitions. Moreover, investment strategies are implemented through unique organizational structures within each SWF, designed to best achieve its irrespective countries national development goals and geopolitical aspirations. The thesis serves as a timely analysis as the region seeks to diversify its economy away from oil revenue and modernize its society, using SWFs as major vehicles of change. Insights from the thesis clarify how SWFs have evolved into pivotal tools for national development, driving economic diversification and enhancing geopolitical positioning in the GCC.